Influence of knowledge of the end-point on pacing during a 2000m rowing time trial - Ferreira, Dean (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2018)
Introduction: A typical 2000 m rowing race requires maximal force production over six to eight minutes. Optimal distribution of energetic resources during such a race is vital for optimal performance. There is little research examining the pacing strategies employed by rowers, particularly at the sub-elite level. Aim: The purpose of this investigation was to determine the influence of knowledge of the end-point on pacing during a 2000 m rowing time trial. Methods: Eleven male rowers from a university rowing club volunteered to partake in the study. Each participant completed three experimental trials on an indoor rowing ergometer, each 2000 m. The only difference between the trials was the nature of the information provided beforehand. At the start of the control trial, participants were correctly informed about the distance to be covered. Participants were not informed of the distance to be completed in the unknown trial. For the deceptive trial, participants were told 1000 m would be completed, but when this distance was reached, they were told to continue for another 1000 m. During each trial muscle activity, power output, heart rate, performance time and perceptions of effort were measured.Results: The control trial was significantly (p<0.05) faster than both the unknown and deceptive trials, however the deceptive trial was the fastest of all trials at the 1000 m distance. The unknown trial was slowest at 1000 m and at 2000 m. Muscle activity, RPE, heart rate and power output were significantly (p<0.05) lower in the unknown trial compared to the control and deceptive trial. The control trial exhibited a reverse J-shape pacing profile. The deceptive trial revealed a significant (p<0.05) reduction in performance time, heart rate, power output and muscle activity after the 1000 m interval. The first 500 m interval had the fastest performance and highest power output in all trials. In all trials, RPE was highest at the end of the 2000 m, the greatest reading being obtained at the end of the control trial. During the first 1000 m of the deceptive trial, the dependant variables were similar to those in the control trial. Once the deception was revealed, there was a significant (p<0.05) reduction in the muscle activity, heart rate and power output. Conclusion: The results of this study indicate that accurate end-point information is crucial to the development of an optimal pacing strategy, and ultimately to successful performance. Rowers tend to adopt the reverse J-shape pacing profile most often due to the tactical and physiological benefits offered by this strategy. Unknown or inaccurate end-point information resulted in performance decrements due to the uncertainty associated with the exercise bout.
Keywords: Rowing -- Training; Rowing -- Coaching; Endurance sports -- Training; Rowers -- Ability testing; Rowing -- Training -- Psychological aspects